Stress Analysis of Cup Flexspline based on Different Model - Wang Changlu; Wei Leyu; Zhang Liyong; Qiao Xuetao; Liu Xinmeng (Jixie chuandong, 2017)
In view of the stress of flexspline calculated on the basis of the theory of thin-walled cylinder,there are many assumptions of the theory,which will lead to the difference between the calculated value and the actual value. Considering the boundary constraint and force,from theoretical model to actual model,six analysis model are constructed based on the geometric model of flexspline to research the difference between theoretical and actual by finite element method. The result of analysis indicate that the maximum value appears in the gear root which is close to the cup bottom of flexspline,and accompanying the transition from theoretical model to actual model,the stress of all direction is increased gradually,which the circumferential stress has a larger increasing range. The reason of that is the stress concentration caused by the boundary constraint.